Micro, Small, and Business Development Model Middle School (MSMEs) in Riau Province - Larbiel Hadi (Inovbiz: Jurnal Inovasi Bisnis, 2023)
Law of the Republic of Indonesia Number 20 of 2008, has mandated that Micro, Small and Medium Enterprises or abbreviated as UMKM need to be empowered by: a) cultivating a business climate that supports the development of Micro, Small and Medium Enterprises; b) development and fostering of Micro, Small and Medium Enterprises. From the results of the study and analysis of Micro, Small and Medium Enterprises in Riau Province, it can be recommended that an appropriate development model be carried out, including Corporate Social Responsibility (CSR), namely a concern or partnership program carried out by companies with micro, small and medium business groups. In this partnership, the company will act as a foster father by providing assistance and guidance through an empowerment program. Next is the microcredit development program, is a business credit granting program aimed at a community that runs a business to increase income with the hope of achieving a better standard of living. And the next one is the cluster development model. This MSME development model is basically to form an MSME industrial center area. By taking into account the potential of the existing area.Keywords: Small and Medium Micro Enterprise Development Model, CSR, Micro Credit Development Program, Cluster Development Model